UJI EFEKTIVITAS LARVASIDA EKSTRAK DAUN KELOR (Moringa oleifera) TERHADAP MORTALITAS LARVA VEKTOR DEMAM BERDARAH DENGUE Aedes aegypti - Rahmaningtyas, Dewinda; Pakan, Prisca Deviani; Setianingrum, Elisabeth Levina Sari (Cendana Medical Journal, 2022)
Background. Dengue Hemorrhagic Fever is a disease caused by the dengue virus through the Aedes aegypti vector. The use of synthetic insecticides as larvicides is still ineffective because it caused environmental problems and target insect resistance. An alternative effort to overcome these negative impacts is to use biolarvicides from Moringa oleifera leaf extract which is more environmental friendly. The content of secondary metabolite compounds such as alkaloids, saponin, tanin and flavonoid in Moringa oleifera leaves can be used as biolarvicides which cause the death of larvae. Objective. To determine whether or not there is a larvicidal effect of Moringa’s leaf extract as biolarvicide against the death of Aedes aegypti mosquito larvae. Methods. Moringa’s leaf extract was made by maseration technique with 70% ethanol as the solvent. Phytochemical test was done to define the secondary metabolite Moringa’s leaf extract contain. 700 larvaes in III/IV stage of Aedes aegypti were used and divided into 7 groups which were positive control gorup with 100 ppm abate,negative control with aquadest and Moringa’s leaf extract group with increasing dose starting at 750 ppm, 1500 ppm, 2250 ppm, 3000 ppm, and 3750 ppm. Observation on the larval death was done in 24 hours with 4 replication. Results. The result of phytochemical analysis show that the extract contains alkaloid, saponin, terpenoid, saponin and tanin. The highest avarage of larval death was found in the highest concentration of the extract (3750 ppm), which is 19,5 larval death for Aedes aegypti. The result of Kruskall Wallis analysis showed that Moringa’s leaf as biolarvicide had a larvicidal effect on killing Aedes aegypti larvae (p=0,000). Using Probit Analysis LC50 of the extract for Aedes aegypti is 3589 ppm and LC99 is 10391 ppm . Conclusion. Moringa’s leaf extract as biolarvicide has a larvicidal effect on the mortality of Aedes aegypti larvae. Keywords : Moringa oleifera leaf, Aedes aegypti, Biolarvicide